Modelling the dynamics of production line control systems in the context of technological safety - Pihnastyi, Oleh; Khodusov, Valery (Akademia Pomorska, 2019)
The report analyzed the multi-section conveyor systems and made a forecast of technological accidents of transport systems. The causes of technological accidents are shown.
Keywords: production line; production control system; PDE-model; flow production